Production of radioactive isotopes by photonnuclear reactions using the MT-22 microtrona - O.D, Maslov; S.N, Dmitriev; A.V, Sabelnikov; M.V, Gustova; L.G, Molokanova; L.G, Molokanova; A.G, Belov (Scientific transaction of the National University of Mongolia. Physics, 2022)
The wide circulation of application of radioisotopes in nuclear medicine, biochemical behavior of elements and environmental would be impossible without development of new methods for theirs of production. The FLNR MT-25 microtron is an important installation for the production of wide variety of man-made radioactive isotopes. On propose of academician of Flerov G.N. in 1980 year experiment were started at the microtron for producing of 123I.